Comprehensive geriatric assessment is useful in an elderly Australian population with diffuse large B‐cell lymphoma receiving rituximab‐chemotherapy combinations. (17th June 2019) - Ong, Doen Ming; Ashby, Michael; Grigg, Andrew; Gard, Grace; Ng, Zi Y.; Huang, Huayi (Ellen); Chong, Yee Shuen; Cheah, Chan Yoon; Devitt, Bianca; Chong, Geoffrey; Loh, Zoe; Mo, Allison; et al.
Summary: Elderly patients may be heterogeneous in their abilities to tolerate immunochemotherapy‐associated toxicities. We describe the morbidity of rituximab‐chemotherapy combinations among 205 newly‐diagnosed diffuse large B‐cell lymphoma (DLBCL) patients aged ≥60 years from 3 tertiary hospitals between 2009 and 2016, and explore the utility of retrospectively‐assigned baseline Comprehensive Geriatric Assessment (CGA) in predicting these toxicities. Seventy‐three percent (146/201) experienced grade ≥3 toxicities, 81% (163/201) needed admission, 52% (107/205) had ≥2 unplanned admissions, 82/201 (41%) required dose reductions (DR) subsequent to Cycle 1, 39/166 (23%) had chemotherapy delays and 26/198 (13%) ceased therapy early. CGA was associated with pre‐emptive baseline DR and perhaps because of this, did not predict grade ≥3 toxicities, ≥2 unplanned admissions or subsequent DR. Three‐year overall survival (OS) of CGA‐fit, CGA‐unfit and CGA‐frail patients was 82%, 60% and 53%, respectively. Three‐year progression‐free survival (PFS) of CGA‐fit, CGA‐unfit and CGA‐frail patients was 66%, 58% and 46%, respectively. OS of CGA‐fit patients was not statistically different from CGA‐unfit patients, but was superior to CGA‐frail patients (hazard ratio 2·892, 95% confidence interval 1·275–6·559, P = 0·011). PFS differences were not statistically significant. Baseline DR and early therapy cessation were associated with inferior OS and PFS independent of CGA. Prospective studies are needed to confirm if CGA‐adapted treatment strategies minimize morbidity and improves survival.